A imagem do cinema japonês : política e ética do olhar e do corpo - Kunigam, André Keiji (2009)
Starting from one of the most imperative among the signifiers of the so-called contemporary globalization the identity this dissertation has as its initial aim an investigation of the ties that made possible the bonding between individuals, their bodies and their nation-states, through modernity and its great vision machine, the cinema. Tha Japanese cinema emerged as one of the most privileged objects of investigation of these bonds for being one of the most canonized and commented national cinematographies, always regarded as extremely particular and distinct. Considering the basic notion that identity and difference are highly political and interdependent productions, propiciated by the various modes of subjectivation of the modern power, we unveiled firstly the historical constitution of the object Japanese cinema as an interiority of culture and tradition, and, subsequently, we looked at the politization of life and body in an aesthetics of biopower. However, eventually, we also managed to reach possible ways of resistence through image, with the film Ichi, the Killer (Koroshiya Ichi, 2001), by Takashi Miike. In four chapters, which undertook a wide historical and conceptual journey, we displayed the convergence of ethics, aesthetics and politics in Japanese cinema: from the biopolitical productions of an identity to the resistent aesthetics of a contemporary cinema. Finally, the dissertation attempted to shed light upon the passage of a cinema of the pedagogy of the look and the body image as representation and body as continent of a transcendent truth to another one, sensuous and destructurating image as presentation and body as immanent affective matter.